Dynamics and control policies analysis of semi-active suspension systems using a full-car model. (27th December 2007) - Ihsan, S.I.; Faris, Waleed F.; Ahmadian, M.
Several control policies of semi-active systems, namely skyhook, groundhook and hybrid controls, are presented. Their ride comfort, suspension displacement and road-holding performances are analysed and compared with passive systems. The analysis covers both transient and steady-state responses in the time domain and transmissibility response in the frequency domain. The results show that the hybrid control policy yields better comfort than a passive suspension, without reducing the road-holding quality or increasing the suspension displacement for typical passenger cars. The hybrid control policy is also shown to be a better compromise between comfort, roadholding and suspension displacement than the skyhook and groundhook control policies.